Proposal to analyze the incidence of the cooperative sector of Valle del Cauca in the fulfillment of the 2030 Sustainable Development Goals - mejia, antonio (Cooperativismo & Desarrollo, 2022)
This article is part of the doctoral research called "Incidence of cooperative systems in social development processes". The fundamental objective of this article is to show how the Colombian cooperative sector affects the fulfillment of the sustainable development objectives (SDG) in Valle del Cauca, Colombia. The methodology used is mixed, the method used is triangulation and consists of carrying out a triangulated analysis of the information collected through various collection techniques, including semi-structured interviews with directors of 12 cooperative organizations (CO) and union directors; content analysis is carried out on these. Additionally, documentary analysis is made of social balance reports of 54 COs, the corresponding examination of aggregated databases for public use is also carried out, such as the financial statement report of COs, presented by the Superintendence of the Solidarity Economy of Valle del Cauca and the population data presented by the National Administrative Department of Statistics (DANE). The result of the research shows us that cooperative organizations do not monitor results aimed at establishing the level of compliance with the SDGs 2030 from their operational planning, although they do recognize in their operational development the fulfillment of many of these goals. Particularly those related to the reduction of poverty, the improvement of education, and the reduction of inequalities.